2022
DOI: 10.1007/s12039-022-02046-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying polypharmacology approach for drug repurposing for SARS-CoV2

Abstract: Exploring the new therapeutic indications of known drugs for treating COVID-19, popularly known as drug repurposing, is emerging as a pragmatic approach especially owing to the mounting pressure to control the pandemic. Targeting multiple targets with a single drug by employing drug repurposing known as the polypharmacology approach may be an optimised strategy for the development of effective therapeutics. In this study, virtual screening has been carried out on seven popular SARS-CoV-2 targets (3CL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…The docking data suggests that neither GRL-0617 or DDL-701 (Figure 5A and B, respectively) interacts with the active site cysteine-111 residue, but rather are bound to the site around tyrosine-268 which lies outside the tunnel containing the active site residue Cys111. DDL-715 and the reported PL pro inhibitor losartan [22] bind the enzyme similarly to DDL-701, at the site around Tyr268 and at the entrance of the active site tunnel leading to Cys111 (Supplementary Figures S3 and S5, respectively).…”
Section: Modeling and Docking Reveal Ddl-701 And Known Pl Pro Inhibit...mentioning
confidence: 94%
See 1 more Smart Citation
“…The docking data suggests that neither GRL-0617 or DDL-701 (Figure 5A and B, respectively) interacts with the active site cysteine-111 residue, but rather are bound to the site around tyrosine-268 which lies outside the tunnel containing the active site residue Cys111. DDL-715 and the reported PL pro inhibitor losartan [22] bind the enzyme similarly to DDL-701, at the site around Tyr268 and at the entrance of the active site tunnel leading to Cys111 (Supplementary Figures S3 and S5, respectively).…”
Section: Modeling and Docking Reveal Ddl-701 And Known Pl Pro Inhibit...mentioning
confidence: 94%
“…Recent studies suggest that the virus could develop resistance to nirmatrelvir through development of mutations in the protease M pro , a phenomenon observed with many antiviral drugs [18,19]. This has raised interest in the development of protease inhibitor cocktail therapy for SARS-CoV-2 [20][21][22][23][24][25][26][27] to increase efficacy and reduce the risk of rebound, which is modeled on the use of protease cocktails for the treatment of HIV and hepatitis C. Use of a protease inhibitor cocktail could help reduce or prevent resistance by making it harder for the virus to evolve around multiple inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Redocking studies were executed to validate the compounds showing the best binding energy obtained by blind docking. We analyzed the active site residues of all three targets from available literature [ 23 , 24 ] and performed individual ligand docking and MLSD with the above protocol [ 25 , 26 ]. The best poses were selected based on maximum interactions depicted for minimum binding energy conformations, and these interactions between protein–ligand complexes were then visualized using the Discovery studio software.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that dihydroergotamine and ergotamine are having stable interactions with 3CL pro and also it has the polpypharmacology e cacy [46]. In addition, the drugs tirilazad and venetoclax was reported to show stable binding a nity towards multiple targets for SARS-CoV2 which indicates their polypharmacology property suggesting them as potential candidate for drug repurposing [35,47].…”
Section: Analysis Of Drug Molecules In the Active And Inactive Datasetmentioning
confidence: 99%
“…Four drugs (i.e., venetoclax, tirilazad, acetyldigitoxin, and ledipasvir) were chosen based on the docking scores, binding pose and the interaction pattern with the SARS-CoV2 targets [35]. In arriving at the drug repurposing a consensus scoring approach has been adopted [36].…”
Section: Introductionmentioning
confidence: 99%